Prevalence of cancer in Takotsubo cardiomyopathy: Short and long-term outcome. (1st July 2017) - Sattler, K.; El-Battrawy, I.; Lang, S.; Zhou, X.; Schramm, K.; Tülümen, E.; Kronbach, F.; Röger, S.; Behnes, M.; Kuschyk, J.; Borggrefe, M.; Akin, I.
Abstract: Background: Takotsubo Cardiomyopathy (TTC) is a transient disorder of ventricular wall dysfunction, mostly induced by physical or emotional stress. TTC may be associated with adverse cardiac events. The association of cancer and its clinical impact in TTC patients has not been described yet. Methods: In 114 consecutive patients presenting with TTC between January 2003 and September 2015, we studied the frequency of cancer diagnosis, and compared the clinical course and the occurrence of a clinical endpoint of cancer and non-cancer patients during a follow up of 4.2 years. Results: Of the 114 patients, 16 (14.0%) had a malignancy already diagnosed at TTC, and further 11 patients received the diagnosis during follow up. Cancer patients had higher frequency of atrial fibrillation and lower hemoglobin levels at admission than patients without cancer. While the occurrence of in-hospital events was comparable, the diagnosis of cancer at TTC event or during follow up was predictive for a higher rate of the composite endpoint. In the Kaplan-Meier analysis, malignant diseases were strongly associated not only with overall mortality but also with worsened time of event-free survival during the long-term outcome. Conclusions: Prevalence of malignant diseases is high in TTC patients, and is a risk factor for worse outcome. Screening for malignancies should be recommended in all patients presenting with TTC. Further studies are needed to define the association on molecular levels.